Bunga Bank Dalam Perspektif Hukum Ekonomi Syariah (Studi Kasus di Desa Sukarasa Kecamatan Pangatikan Kabupaten Garut) - Sofiawati, Eva; Sulaeman, Yusup (STAI Al Musaddadiyah Garut, 2022)
Economic problems greatly affect community life. Some overlook the truth about halal and haram, as long as their daily needs are met. This is what happens in some communities in Sukarasa Village, Pangatikan District, Garut Regency. They are willing to borrow money even though there is a large interest that they have to repay later. The aim of this research is to determine the practice of usury (bank interest) carried out by non-bank financial institutions in Sukarasa Village, Pangatikan District, and to understand the perspective of Islamic economic law on the practice of usury (bank interest) by the community of Sukarasa Village. This research is a field research with a descriptive qualitative approach. The approaches used are normative theological, formal juridical, and phenomenological approaches. Data collection techniques include observation, interviews, and documentation. Data analysis techniques involve data reduction, data display, and concluding drawing/verification. The results of this study show that some of the community members in Sukarasa Village, Pangatikan District, consider the interest charged by non-bank financial institutions to be the same as bank interest and thus considered usury. However, they do not use this as a reason not to take out loans because they are pressed by the need for economic fulfillment. The interest charged by non-bank financial institutions has a negative impact on the people of Sukarasa Village, as the high interest rates have not improved their economic lives; instead, they have become increasingly impoverished and dependent on these institutions because they have to take out loans again to cover the interest on their previous loans. Keywords: bank interest, perspective, Islamic economic law